Qualidade de vida de pessoas com transtornos mentais cumprindo medida de segurança em hospital de custódia e tratamento - Ana Flavia Ferreira de Almeida Santana (2008)
Introduction: The judicial mental hospitals, institutions to care for and treat patients with mental disease who committed crimes and are in the custody of law courts. In the last 15 years, there has been a growing interest in studies on the quality of life (QL) of patients with mental disorders due to the diseases impact. The patients own perception of their lives condition has contributed to build priorities in treatment and to serve as a stimulus so that the health programs can care for the quality of life of these people. Objective: Investigate the QL of patients with schizophrenia who are institutionalized under safety order, seeking to identify indicators that may guide treatment and intervention necessary under the current mental health policies in effect in Brazil. Material and Method: A cross-section study was carried out involving 54 patients in a Custodial and Treatment Hospital in Barbacena, State of Minas Gerais. The interviews were carried out with the patients themselves as informants. The following instruments were used: a socio-demographic questionnaire with information about the diagnostic, clinical history, crime history, personal and socio-demographic characteristics and the QLS-BR (Quality of Life Scale), specific for the evaluation of the quality of life of patients diagnosed as schizophrenic. The data were analyzed statistically according to the Statistics Package for Social Sciences (SPSS version 11.0). A descriptive analysis of the data was conducted; using central tendency and dispersion measures. The association between the quality of life scores was used through a multivariate analysis, using a decision tree as a tool, with a CHAID algorithm. Results: The majority of the patients is male, with paranoid schizophrenia more than ten years; have not concluded the basic education and have not spouse and have practiced professional activities without qualification. The majority of them is under safety order due to have committed homicide. This study showed a low quality of life of patients institutionalized under a safety order. All the domains, including the global, showed scores indicating a very compromised quality of life. The occupational domain was the most compromised. Patient who present a higher time of duration of the disease, have been committed homicide and be more than 40 years old were factors associated with the low QL of the patients from the multivariated analysis. Conclusion: The study indicates the need for actions to break the stigma of danger of offending madmen and provide policies compatible with a more dignified and humanitarian treatment of these patients as well. They are institutionalized patients under safety order and also have the medical diagnosis of schizophrenia, a disease that affects QL, provoke impact in people lives and increase their vulnerability to stressful and problematic daily situations.